Mesoporous zeolites as catalysts for the production of specialty and fine chemicals - Endud, Salasiah; Hamdan, Halimaton; Mohd. Muhid, Mohd. Nazlan; Ramli, Zainab (Faculty of Science, 2007)
The mesoporous molecular sieves MCM-41 and MCM-48 have been hydrothermally synthesized from rice husk ash as an active source of silica in the presence of organic surfactant as structure-directing agent. The surfactant-templated approach has created periodic porosity as well as catalytic functions (acid-base, redox and host for catalytically active sites) in the molecular sieve catalysts. A deliberate design of pores is possible in the pore size range of 2 to 10 nm with controlled chemical compositions and structures. Mesoporous oxides in which metals (Ti, Zr, V, Nb, Mo, W, Mn, Fe, Co, Sn, Li, Cs, La) partially substitute for silicon in the porous network of MCM-41 and MCM-48 were prepared via two routes: (i) the post synthesis thermal treatment of silica mesophases by the â€œmolecularly designed dispersionâ€ technique and, (ii) the in situ synthesis of framework incorporated metal ions. The resulting materials were characterized with various techniques: XRD, FTIR, DRUV-Vis, ESR, 14Li, 13C, 27Al and 29Si MAS NMR spectroscopy, FESEM, TEM, AAS, TG-DTA, TPDRO, surface acidity using probe molecules, BET and N2 adsorption isotherms. Highly-ordered mesoporous materials with all of the appropriate catalytic requirements including large surface areas (>1000 m2g-1) and pore volumes (0.9-2.0 cm3g-1) readily accessible to large molecules have therefore been produced. The mesostructured silica materials could form spherical or fibrous rodlike morphologies depending on reaction conditions. The catalysts have been optimized for stability, activity, and selectivity in batch processes. The mesoporous materials possessed high thermal and hydrothermal stability similar to that of microporous zeolite-based catalysts and the atomic ordering in the pore walls remained intact during various stages of the preparation. The metal oxide modified mesoporous catalysts displayed extraordinarily high activity and selectivity in liquid phase oxidation of aromatic alcohol using H2O2 as oxidant under mild conditions with or without the presence of solvent. Furthermore, the metal leaching by solvent was observed to be negligible suggesting that the catalyst could be recycled. Mesoporous materials MCM-41 and MCM-48 with aluminium in the framework were selective acid catalysts in the Friedel-Crafts acylation of aromatic compounds while metal organic complexes encapsulated in the mesopores effectively catalyzed the one step oxidation of benzene to phenol. Also bifunctional catalysts with highly dispersed acidic and redox active sites were achieved when acidic mesoporous catalysts were incorporated with metal oxide particles such as NbOx, TiOx and LnOx with different loading through ion exchange and impregnation method. The synergistic effects of the two functions have enabled highly selective aldol, nitroaldol and Claisen-Schmidt condensation of aldehyde and epoxidation of alkene, that have never been possible using traditional catalysts employing either Lewis or BrÃ¶nsted acidity alone. On the other hand, silylated mesoporous silica materials were hydrophobic, and performed well as matrices for immobilization of conducting polymer and polymer electrolyte. Polymer modifications on MCM-41 and MCM-48 by in situ synthesis, miniemulsion polymerization, melt and solution intercalation methods yielded polymeric nanocomposites with enhanced thermal stability as well as catalytic, optical, conducting or dielectric properties. In addition, zeolite/mesoporous molecular sieve composites were also synthesized as an alternative approach to increasing the acidity of MCM-41 and MCM-48 catalysts for high temperature acid catalysis of reactions such as cracking and hydrocracking.